Zimbabwe Public Expenditure Review with a Focus on Agriculture - World Bank (World Bank, Washington, DC, 2019)
This report examines agricultural spending in Zimbabwe. This public expenditure review (PER) is the sixth in a series focusing on local government service delivery, state-owned enterprises and parastatals, education, social protection, and cross-cutting issues. The PERs are intended to support the Government of Zimbabwe in improving its fiscal management. Agriculture plays a critical role in Zimbabwe’s economy. About two thirds of Zimbabweans work in agriculture and many Zimbabweans, directly or indirectly, depend on it. Public spending on agriculture needs to be understood against the backdrop of Zimbabwe’s history of land reform. Between 2011 and 2015, spending on agriculture had been broadly comparable to other countries. Government introduced the new program, command agriculture, in 2016-17 in order to reverse decline in agricultural production. Sustainable agricultural spending cannot be separated from structural reforms to raise agricultural productivity and rebuilding of macroeconomic resilience. Some steps to rebuild resilience have already been undertaken in 2019, but the fiscal cost of agriculture has proven difficult to contain.